PENEGAKAN HUKUM LINGKUNGAN TERHADAP KERUSAKAN LINGKUNGAN (STUDIKASUSPUTUSAN MAHKAMAH KONSTITUSI NOMOR 55/PUU-XIX/2021) - Wahyu rasyid, Hartono Hamzah, Muhammad Dede Febriansyah (Madani Legal Review, 2023)
This study aims to analyze and find out about Environmental Law Enforcement Against Environmental Damage (Case Study of Constitutional Court Decision Number 55/PUU-XIX/2021). Then it is explained into several sub-problems or research questions, namely first How is environmental law enforcement related to cases of environmental damage, and How is the Ideal Concept in the Application of the Job Creation Law Related to the Constitutional Court Decision Number 55/PUU-XIX/2021. This research is a literature study using a normative approach and a qualitative method approach. The results of this study indicate that environmental protection and management (PPLH permit) can be considered a violation of environmental permits, based on article 76 of Law 32/2009 concerning PPLH where the Minister/Governor/Regent The Mayor can apply administrative sanctions to business actors in accordance with their authority if during the implementation of supervision a violation of environmental protection and management permits is found where administrative sanctions are found. And as for the Ideal Concept in the Application of the Job Creation Law Related to the Constitutional Court Decision Number 55/PUU-XIX/2021, a number of laws have been amended by the Job Creation Law, the original/origin laws of each are still remains in force – even though the applicability of the old law is not confirmed in the Job Creation Law. Meanwhile, in the old law the principles and objectives of each law were determined, which were then elaborated into the norms of the articles regulated in each of these laws. Then, regarding the principle of openness.